2019
DOI: 10.1093/qje/qjz021
|View full text |Cite
|
Sign up to set email alerts
|

Firm-Level Political Risk: Measurement and Effects*

Abstract: We adapt simple tools from computational linguistics to construct a new measure of political risk faced by individual U.S. firms: the share of their quarterly earnings conference calls that they devote to political risks. We validate our measure by showing that it correctly identifies calls containing extensive conversations on risks that are political in nature, that it varies intuitively over time and across sectors, and that it correlates with the firm’s actions and stock market volatility in a manner that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
420
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 732 publications
(563 citation statements)
references
References 93 publications
14
420
0
3
Order By: Relevance
“…Rather, we see our policy experiments as a means to document and quantify the effects of such policies in times of heightened uncertainty. It is also worth noting that this ignores the direct impact of policy on uncertainty as studied by papers such as Baker, Bloom, and Davis (2016) and Hassan, Hollander, van Lent, and Tahoun (2017).…”
Section: Policy In the Presence Of Uncertaintymentioning
confidence: 99%
“…Rather, we see our policy experiments as a means to document and quantify the effects of such policies in times of heightened uncertainty. It is also worth noting that this ignores the direct impact of policy on uncertainty as studied by papers such as Baker, Bloom, and Davis (2016) and Hassan, Hollander, van Lent, and Tahoun (2017).…”
Section: Policy In the Presence Of Uncertaintymentioning
confidence: 99%
“…It is well-recognized in both theoretical and empirical work that uncertainty can directly influence firm-level investments and employment (Pindyck, 1988;Bernanke, 1983;Dixit and Pindyck, 1994;Bloom et al, 2007). Furthermore, recent developments in the literature have highlighted that first and second moment shocks can appear together, either amplifying or confounding each other (Bloom et al, 2018;Berger et al, 2017;Hassan et al, 2019). We examine these predictions in the context of Brexit, which (it has been argued) represents an "almost ideal" uncertainty shock inasmuch as it was large, unanticipated, and delayed in implementation (Fisman and Zitzewitz, 2019;Born et al, 2019).…”
Section: The Firm-level Effects Of Brexitmentioning
confidence: 99%
“…While prior studies have shown that uncertainty has far-reaching consequences on firm policies of first order importance (such as investments and hiring), this work has been hampered by the lack of "sound, flexible measures of uncertainty" (Altig et al, 2019). Our work highlights the versatility of text-based measures of uncertainty, adding to recent work which pioneered these approaches in the context of political uncertainty (Baker et al, 2016;Hassan et al, 2019) and applied them to themes like trade policy (Handley and Li, 2018;Caldara et al, 2019;Kost, 2019).…”
mentioning
confidence: 92%
“…In online appendix table 12, we examine whether judge ideology's effect varies with firms' political donations(Hassan, Hollander, van Lent, and Tahoun [2017]). Our main findings remain robust after including the firms' political donations and its interaction with LiberalCourt.…”
mentioning
confidence: 99%